Academic Information System at SMA PGRI 2 Palembang Using the Web Engineering Method - Avriwijaya (Jurnal Ilmu Komputer dan Sistem Informasi |JIKSI|, 2023)
SMA PGRI 2 Palembang is a private senior high school accredited â€œA,â€ located on Jendral Ahmad Yani Street, Gotong Royong Alley, 9/10 Ulu Subdistrict, Seberang Ulu 1, Palembang City. At this school, academic activities particularly the management of student report cards are still conducted manually (offline). Although such offline management practices are still common among educational institutions below the tertiary level, the rapid advancement of information technology has encouraged schools to adopt systems similar to those implemented in higher education institutions. To enhance efficiency and accuracy in academic data processing, this study proposes the development of an Academic Information System (AIS) specifically designed for managing student report cards online. The system is developed using the Web Engineering method, which ensures a structured, scalable, and user-centered design process. Implementing an online academic information system offers several advantages, including streamlined data management, better data integration, and the creation of a centralized academic information hub. The resulting web-based system enables teachers to input grades and students to access their report cards anytime and anywhere, significantly improving the effectiveness and transparency of academic administration at SMA PGRI 2 Palembang.